Contribution of Computed Tomography Scan to the Diagnosis of Spinal Tuberculosis in 14 Cases in Assaba, Mauritania. (2nd May 2019) - Boushab, Boushab Mohamed; Kone, Noukhoum; Basco, Leonardo K.
Abstract : Background . The incidence of tuberculosis has increased in recent years in both developed and developing countries. Objective . This retrospective study aimed to review all cases of spinal tuberculosis diagnosed at the Department of Internal Medicine and Infectious Diseases in Kiffa Regional Hospital and assess the role of computed tomography (CT) scan in establishing definite diagnosis. Patients and Methods . Data were collected from clinical records of patients admitted to the hospital for rachialgia between August 2016 and July 2018. Results . Fourteen (12.2%) adults with spinal tuberculosis were found among 115 patients with all forms of tuberculosis during the study period. The mean (± standard deviation) age of our patients was 47.5 ± 22.0 years old with male:female (8/6) sex ratio of 1.3. The mean duration of evolution of the disease was 15 months. The presenting signs and symptoms included rachialgia in most patients (93%), associated with segmental spinal stiffness (50%) and/or neurological complications (50%). Diagnosis was established on the basis of clinical history, clinical examination, standard vertebral column radiography, and CT scan. Vertebral imaging showed a clear predominance of lumbar lesions (57%), followed by dorsal (36%) and cervical (7%) involvement. The evolution under treatment was favorable, with the exception of two cases of medullary compression. Conclusion . Spinal tuberculosis is the most common form of osteoarticular tuberculosis. It affects predominantly lumbar and dorsal vertebrae. In the absence of histological confirmation, the presence of back pain associated with major radiological signs of spondylosis disc disease seems to justify the use of CT scan to confirm the diagnosis of this pathology.